OPTIMALISASI PERANAN METODE SIMULASI TERHADAP HASIL BELAJAR PADA PEMBELAJARAN AQIDAH AKHLAK MADRASAH IBTIDAIYAH - Munawir; Elok Maulidah Sofiyah; Yuyun Dwiratnawati (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
In learning Aqidah Akhlak for madrasah ibtidaiyah students it is necessary to have a way to increase students' understanding and ability towards the concept of learning Aqidah Akhlak, thus applying the simulation method in learning is an effective way. The simulation method is a technique in learning that can stimulate students to practice real situations. in a controlled environment. This study aims to be able to find out the results of the effectiveness of applying the simulation method in teaching aqidah morals madrasah ibtidaiyah students. The results of this study prove that the application of the simulation method in learning aqeedah morals can improve students' understanding and skills significantly. From the results of the study it can be concluded that the application of the simulation method madrasah ibtidaiyah students in teaching morals of aqidah is an effective and innovative learning alternative. Therefore it is suggested that teachers can apply this method in the process of learning morals and aqidah in madrasah ibtidaiyah.